A web demo for basic number theory concepts used in symmetric cryptography (AES) - Zhou, Jingyuan (2017)
This project aims to develop a web based application to demonstrate in detail the mathematics behind the AES (Advanced Encryption Standard) S-Box, namely the computation over Galois Field, in order to help students to better understand the concept. By adopting agile development, the final prototype with main functionalities was already used in class to help the students understanding the concepts.